AN INVESTIGATION OF THE USE OF THE FIRST LANGUAGE IN LIBYAN EFL CLASSROOMS - Alsied, Safia Mujtaba (TEFLIN Journal, 2018)
This article attempts to explore the use of first language (Arabic) in the Libyan EFL classrooms as well as teachers' and students' attitudes towards using it. To this end, 5 Libyan EFL teachers and 143 Libyan EFL undergraduate students from the English department of Sebha University took part in the study. Data were gathered through questionnaires and semi-structured interviews. The findings of the study indicated that the Libyan EFL students had positive attitudes towards using Arabic in the classroom to some degree; however, they were in favor of using English more than Arabic. It was also found that the students employed Arabic frequently to translate words from English into Arabic. The results also reported that the Libyan EFL teachers used Arabic in their classrooms to accomplish many purposes such as helping students to understand, giving instructions, emphasizing information and giving the meaning of new and unfamiliar words. Additionally, teachers held positive attitudes towards the use of Arabic inside the classroom, but they were of the opinion that Arabic can be only used in certain cases and it should not be overused.